1999
DOI: 10.1038/sj.onc.1202278
|View full text |Cite
|
Sign up to set email alerts
|

Human ubiquitous JCV(CY) T-antigen gene induces brain tumors in experimental animals

Abstract: JCV is a papovavirus which is widespread in the human population. The prototype Mad-1 variant of JCV induces a fatal demyelinating disease of the central nervous system (CNS) called Progressive Multifocal Leukoencephalopathy (PML) in immunosuppressed individuals. The unique tropism of JCV (Mad-1) to the CNS is attributed to the tissue-speci®c regulation of the viral early promoter which is responsible for the production of the viral regulatory protein, T-antigen. The archetype form of this virus, JCV(CY), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 35 publications
(19 reference statements)
3
77
0
1
Order By: Relevance
“…The following cell lines were used in this study: mouse medulloblastoma, BsB8, isolated from cerebellar tumor of transgenic mouse expressing an early genome of human polyomavirus JC (Krynska et al, 1999;Wang et al, 2001); and two human medulloblastoma cell lines, D384 Med and Daoy. D384 are metastatic medulloblastomas isolated from peritoneal ascietes from a boy with medulloblastoma (ATCC# HTB-185), and Daoy derive from a tumor in the posterior fossa of a 4 years old boy (ATCC# HTB186).…”
Section: Cell Culturementioning
confidence: 99%
“…The following cell lines were used in this study: mouse medulloblastoma, BsB8, isolated from cerebellar tumor of transgenic mouse expressing an early genome of human polyomavirus JC (Krynska et al, 1999;Wang et al, 2001); and two human medulloblastoma cell lines, D384 Med and Daoy. D384 are metastatic medulloblastomas isolated from peritoneal ascietes from a boy with medulloblastoma (ATCC# HTB-185), and Daoy derive from a tumor in the posterior fossa of a 4 years old boy (ATCC# HTB186).…”
Section: Cell Culturementioning
confidence: 99%
“…In earlier studies to unravel the biological function of JCV T-antigen, we created transgenic animals expressing the JCV early protein via the viral early promoter. Several lines developed tumors in the cerebellum, which were classified as medulloblastomas based on the location and expression of marker proteins (Krynska et al, 1999b). The expression of T-antigen was detected in tumor mass, and in cell lines derived from the tumor (Krynska et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Of interest, PCR-based and immunohistochemical detection of the JC virus (JCV) genome and viral proteins, including JCV T-antigen, has raised questions about the contribution of this common polyomavirus to the development of medulloblastoma. [12][13][14][15] The genomic alterations and possible viral contribution suggest that mechanisms responsible for the maintenance of genomic integrity could be compromised in medulloblastomas. One feasible connection to the development of genomic instability is JCV Tantigen.…”
mentioning
confidence: 99%
“…Although its role in the etiology of human tumors is still controversial, JCV T-antigen readily transforms cells in culture and is tumorigenic in experimental animals. 8,14,[16][17][18] In addition to the well-established effects of SV40, BKV and JCV T-antigens in deregulating the cell cycle, 19 these viral proteins are suspected to play a role in the development of genomic instability. Several studies have shown random chromosomal aberrations emerging at each consecutive passage of T-antigen positive cells.…”
mentioning
confidence: 99%